Transmission Channels of Central Bank Asset Purchases in the Irish Economy - Cormac Cawley; Marie Finnegan (Economies, 2019)
The European Central Bank (ECB) engaged in an expanded asset purchase programme (APP) from 2014 to 2018 to help achieve their primary objective of price stability. Total assets purchased over this period was over €2.5 trillion and new net purchases ended in December 2018. This paper identifies whether the ECB’s APP in Ireland operated through the portfolio rebalancing channel, the signalling channel or the lending channel. It presents a quantitative descriptive analysis of some key Irish data sets in the 2014–2018 period and uses time-series visualisation and trend analysis to identify trends and correlations. There are a number of preliminary findings. First, much downward pressure on sovereign debt yields and spreads had occurred before the APP began due to previous accommodative monetary policy and the signalling channel. Second, the corporate-sector purchase programme (CSPP) did impact on targeted bonds and may have had spill overs to non-targeted bonds. Third, the APP did not lead to much increased lending to the SME sector. Fourth, while households did engage in traditional portfolio rebalancing, Irish banks did not and were perhaps more motivated to meet their capital requirements and manage their level of reserves. This is a first step towards understanding the transmission channels of ECB policy in Ireland and more work needs to be done to detangle the transmission of the most recent APP from other factors and consider these findings in the context of theoretical models. Such work is important to help inform policy makers on enhancing the transmission mechanism to the Irish economy of the recently launched new ECB asset purchase programme from November 2019.